(untitled) (CAHIERS MAGELLANES-NS, 2024)
The different extracts have been assessed for their potential in vitro antibacterial and antiviral capabilities. The essential oil was analyzed by GC-EIMS, resulting in the discovery of 92 components that accounted for 96.1% of the oil. The primary constituents included 1,8-cineole, a-pinene, caryophyllene oxide, and sabinene. The hexane and dichloromethane extracts exhibited no antibacterial action. The methanolic extract and essential oil shown varying levels of effectiveness against the bacteria tested. The antiviral efficacy of the plant samples was evaluated using two model systems: the replication of two influenza viruses in MDCK cells and the replication of two herpes simplex viruses in MDBK cells. The methanol extract had a potent antiviral action against the influenza virus, resulting in a considerable reduction in the growth of both A/Weybridge and A/Aichi strains. This extract also demonstrated antiviral efficacy against the herpes virus. The concentration of total phenolics in the methanol extract was significantly high. Dichloromethane was the subsequent substance. This extract has also been discovered to contain a high concentration of flavonoids. An affirmative association was detected between the potential for biological activity and the quantity of phenolic chemicals present in the extracts.